OPTIMALISASI DIGITAL MARKETING MIE GACOAN MELALUI KONTEN KREATIF COPYWRITING PADA AKUN INSTAGRAM @mie.gacoan - Julyanto Ekantoro; Fitria Widiyani Roosinda; Fikriyah Afi Nabilah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
Copywriting is an important part of marketing through digital marketing. So, gacoan noodles also apply creative content in their marketing through copywriting. In creating creative content on his Instagram account, creativity is needed. This study aims to examine how to optimize digital marketing of mie gacoan through creative copywriting content on the @mie.gacoan account. This study used qualitative descriptive research methods and interview techniques with the Maintenance & Repair Manager who is also the Operational Incharge Handle at the Wiyung Surabaya branch of mie gacoan, as well as making observations on the @mie.gacoan account related to optimizing the digital marketing of mie gacoan through creative copywriting content on the @mie.gacoan account. The results show that the optimization of digital marketing of creative copywriting content to increase consumer buying interest has run optimally, because consumers feel more aware about the products and brands of gacoan noodles. And when the copywriting content related to the change of menu name and the issuance of a statement that gacoan noodles have obtained halal certification from MUI, making sales turnover and customers of gacoan noodles increase. Keywords : Digital Marketing, Instagram, Copywriting